Virtual Reality and Its Application in Environmental Education - Zhou, Ziya (2022)
This paper introduces the basis of virtual reality (VR), describes the benefits of applying virtual reality technology in environmental education, and presents a 360° VR product that focused on whales in Antarctica. According to the results of previous studies in this field, virtual reality can assist environmental education in many ways, including providing an affordable substitute for field trips. However, currently, there are a few challenges that need to be resolved. The product of this study was produced by multiple computer software systems, containing nine scenes of 360° videos or panoramas with interactive features. This VR product can serve as a tool for entry-level learners of marine science to acquire information about Antarctica, Antarctic minke whales, and climate change, in a compelling and fun way. In conclusion, it is practical and beneficial to apply virtual reality as a tool in environmental education.